Antimicrobial Resistance and Molecular Epidemiology of Uropathogenic Escherichia coli Isolated From Female Patients in Shanghai, China - Zeng, Qian; Xiao, Shuzhen; Gu, Feifei; He, Weiping; Xie, Qing; Yu, Fangyou; Han, Lizhong (Frontiers in Cellular and Infection Microbiology, 2021)
Urinary tract infection (UTI) is one of the most common bacterial infections and UTI is the most common extraintestinal infectious disease entity in women worldwide. Uropathogenic Escherichia coli (UPEC) is the leading cause of UTI. While antimicrobial resistance has emerged as one of the principal problems of UTI, little is known about the epidemiology of UPEC isolated from female patients in Shanghai. This study aimed to describe the antimicrobial resistance and molecular epidemiology of UPEC isolated from female patients in Shanghai, China. UPEC isolates were collected from female patients during July 2019 to June 2020 in Shanghai and total 151 isolates were obtained randomly. Antimicrobial susceptibility testing was performed using disk diffusion method. Multilocus sequencing type, phylogenetic groups, antimicrobial resistance genes and virulence genes were detected by polymerase chain reaction. In our study, no carbapenem-resistant isolates were found, but fluoroquinolone-resistant and muti-drug resistant UPEC accounted for 62.25% and 44.37%, respectively. The phylogenetic group B2 (58.94%) predominated, followed by phylogenetic group D (26.49%). And the most prevalent sequence type was ST1193 (25.83%), which first reported in Shanghai. Rate of extended-spectrum β-lactamase (ESBL)-positive isolates was 39.73% and the dominant ESBL genotype was blaCTX-M-14 (21/60), followed by blaCTX-M-55 (12/60). Mutations in gyrA were detected in majority of fluoroquinolone-resistant isolates (90/94), followed by parC (85/94) and parE (71/94). Besides, the aac (3) -IIa was found in 85% of aminoglycoside resistance isolates. Among 151 UPEC isolates, the common virulence genes were csgA (97.35%), fimH (92.72%), sitA (82.27%) and malX (65.56%). In conclusion, high antimicrobial resistance of UPEC isolated from female patients, harboring a series of virulence genes, are troublesome for the medical practitioners in Shanghai. At present, the prevalent ST1193 and emerging blaCTX-M-55 make more challenging in UTI therapy.